Tomosvaryella Aczél (Diptera: Pipunculidae) of Colombia, with description of two new species - Ramos-Pastrana, Yardany; Rafael, José Albertino (Zootaxa, 2021)
Tomosvaryella Aczél, 1939 has a cosmopolitan distribution and is a genus well studied in general in the Neotropical Region. However, in Colombia only three species were recorded. Two new species of Tomosvaryella are described from protected areas and from conflict territories of limited access in Colombia, namely: Tomosvaryella macarenensis sp. nov. (type-locality: Serrania Macarena, Meta) and T. martae sp. nov. (type-locality: San Vicente del Caguan, Caquetá). The female of T. tuberculata Hardy, 1948 is described. Tomosvaryella similis (Hough, 1899) is new to South America (Colombia) and T. galapagensis (Curran, 1934), T. lynchi (Shannon, 1927), T. mexicanensis Ale-Rocha & Rafael, 1995, T. similis, T. tuberculata and T. venezuelana Ale-Rocha, 1993 are reported for the first time in Colombia. Illustrations and a dichotomic key to Colombian species of Tomosvaryella are presented. Furthermore, the diagnosis of all species recorded in Colombia are amended. The Tomosvaryella fauna is increased from three to 11 species in Colombia.